COMPARISON OF RENAL PROTECTIVE EFFECTS BETWEEN SGLT2 INHIBITORS AND DPP4 INHIBITORS IN TYPE 2 DIABETES IN REAL-WORLD CLINICAL PRACTICE - Park, Hyeong-Kyu; Park, Sang-Joon; Kwon, Soon-Hyo; Byun, Dong-Won; Suh , Kyo-il (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Recent prospective randomized studies have shown that sodium-glucose cotransporter 2 inhibitors (SGLT2i) had renal protective effects compared to placebo in patients with type 2 diabetes (T2D). In this study, we compared the renal composite outcomes between patients with T2D treated with SGLT2 inhibitors and those treated with dipeptidyl peptidase 4 inhibitors (DPP4i) using real-world clinical data. METHODOLOGY This retrospective observational study used the Observational Medical Outcomes Partnership Common Data Model (OMOP-CDM) database at four different university hospitals (Soonchunhyang University Hospitals in Seoul, Bucheon, Chunan, and Gumi) in Korea. The patients prescribed with SGLT2 inhibitors or DPP4 inhibitors for at least 90 days were included in the SGLT2 inhibitor or DPP4 inhibitor group, respectively. Subjects prescribed GLP-1 receptor agonists or insulin were excluded in both groups. Renal composite outcomes included a 30% decline in estimated glomerular filtration rate (eGFR) compared to baseline or creatinine doubling or dialysis or death from any cause. RESULTS After propensity score matching, clinical characteristics in each group at each hospital were well balanced at baseline. Our results from hospitals in Seoul, Bucheon, and Gumi have shown that SGLT2 inhibitor decreased renal composite outcomes compared to DPP4 inhibitor (hazard ratio (HR) 0.644, p = 0.020; HR 0.560, p <0.001; HR 0.657, p = 0.010, respectively). Furthermore, when all the data were combined, renal composite outcomes were significantly lower in the SGLT2 inhibitor group compared to the DPP4 inhibitor group (HR 0.659, p <0.001). CONCLUSION In conclusion, SGLT2 inhibitors effectively reduce renal composite outcomes compared to DPP4 inhibitors in realworld clinical practice.